What Proportion of Patients Need Extensive Surgery After Failure of the Ponseti Technique for Clubfoot? - Willis, R. Baxter (Springer-Verlag, 2009)
In 1948, Professor Ignacio Ponseti began a nonoperative management form of treatment for severe talipes equinovarus. This method of manipulative treatment became attractive because long-term outcomes demonstrated the majority of feet were pain-free, plantigrade, and functioning at a high level of activity without evidence of degenerative arthrosis. We retrospectively reviewed the charts of 51 children (31 boys and 20 girls; 72 feet) with idiopathic clubfeet deformity treated with the Ponseti method from January 5, 2002, to January 5, 2007. The median age at treatment was 2 weeks (95% confidence limit, 1–2 weeks); there was no difference in age at presentation between boys and girls. The minimum followup was 4 months (mean, 19.8 months; range, 4–48 months). A total of 288 casts were applied (mean, 5.5; standard deviation, 0.92). Successful treatment was defined as a plantigrade foot with a normal hindfoot, midfoot, and forefoot on clinical examination. Correction was achieved and maintained in 90% (65 of 72) of the feet; 10% (seven of 72) of the treated feet did not improve and needed subsequent surgery. There was no difference in the proportion of children who had tenotomy or previous treatment among those who presented with residual deformity or recurrence or had surgery. However, patients who tolerated bracing had lower recurrence rates and underwent less surgery. Level of Evidence: Level IV, therapeutic study. See the Guidelines for Authors for a complete description of levels of evidence.